Penerapan Teknik Reinforcement dan Punishment dalam Bingkai Konseling terhadap Anak-anak Panti Yauma Surabaya - Sukma, Fara Fairuz; Ningtias, Citra Ardiani Dwi Ayu; Murtadlo, Wildan Nasruddin; Habsy, Bakhrudin All (Lembaga Yasin AlSys, 2024)
An analysis of the behavior of children in a twofa orphanage related to engagement in learning activities and talent expression. Through observation and interview methods, internal and external factors such as reinforcement and punishment influence children's level of engagement. Positive stimuli such as appreciation encourage active participation, while negative stimuli such as prohibition from playing games provide motivation for behavior change. The results showed the effectiveness of applying reinforcement and punishment in changing children's behavior to become more active and expressive. In conclusion, this approach has an important role in shaping the character of children in orphanages, encouraging engagement in learning, and talent development.